# Multiplying Binomial by Binomial: Worksheets, Online Test and Calculators

Multiplying binomial by binomial worksheets, solved worksheet problems or exercises with step-by-step work, formative assessment as online test, calculator and more learning resources to learn, practice, assess and master the basic math skills of algebra.

Multiplying Binomial by Binomial
Name
Date

1
Find the product
(6x+5y) ( 4x-9y )

2
Find the product
(a+7b) ( a-5b )

3
Find the product
(4y+4x) ( 4y+3z )

4
Find the product
(5x+2y) ( 9x+2y )

5
Find the product
(5y+4z) ( 4z+6x )

6
Find the product
(6x+2y) ( x+6y )

7
Find the product
(10y+2z) ( 2y+3x )

8
Find the product
(4y-x) ( 6x-y )

9
Find the product
(9a+b) ( 6a-6b )

10
Find the product
(2x-2y) ( 5x-3y )

11
Find the product
(2x+3y) ( 5y-2z )

12
Find the product
(12y+4z) ( 2y+3z )

13
Find the product
(2x+4y) ( 9y-2z )

14
Find the product
(9a+2b) ( 6a+6b )

15
Find the product
(3a+4b) ( 2a+4b )

16
Find the product
(3x+3y) ( 4x+5y )

17
Find the product
(3x+5y) ( x-y )

18
Find the product
(x-4y) ( 2x+3y )

19
Find the product
(7x-y) ( 9x-2y )

20
Find the product
(15m-3n) ( 14m-16n )

Solved Worksheet Problems
Show All Workout
1
Find the product
(6x+5y) ( 4x-9y )

= 24x2-34xy-45y2
Solution
= (6x+5y) x (4x-9y)
= (6x) x (4x) - (6x) x (9y) + (5y) x (4x) - (5y) x (9y)
= 24x2-54xy+20yx-45y2
= 24x2-34xy-45y2
2
Find the product
(a+7b) ( a-5b )

= 1a2+2ab-35b2
Solution
= (a+7b) x (a-5b)
= (a) x (a) - (a) x (5b) + (7b) x (a) - (7b) x (5b)
= 1a2-5ab+7ba-35b2
= 1a2+2ab-35b2
3
Find the product
(4y+4x) ( 4y+3z )

= 16y2+12yz+16xy+12xz
Solution
= (4y+4x) x (4y+3z)
= (4y) x (4y) + (4y) x (3z) + (4x) x (4y) + (4x) x (3z)
= 16y2+12yz+16xy+12xz
4
Find the product
(5x+2y) ( 9x+2y )

= 45x2+28xy+4y2
Solution
= (5x+2y) x (9x+2y)
= (5x) x (9x) + (5x) x (2y) + (2y) x (9x) + (2y) x (2y)
= 45x2+10xy+18yx+4y2
= 45x2+28xy+4y2
5
Find the product
(5y+4z) ( 4z+6x )

= 20yz+30yx+16z2+24zx
Solution
= (5y+4z) x (4z+6x)
= (5y) x (4z) + (5y) x (6x) + (4z) x (4z) + (4z) x (6x)
= 20yz+30yx+16z2+24zx
6
Find the product
(6x+2y) ( x+6y )

= 6x2+38xy+12y2
Solution
= (6x+2y) x (x+6y)
= (6x) x (x) + (6x) x (6y) + (2y) x (x) + (2y) x (6y)
= 6x2+36xy+2yx+12y2
= 6x2+38xy+12y2
7
Find the product
(10y+2z) ( 2y+3x )

= 20y2+30yx+4zy+6zx
Solution
= (10y+2z) x (2y+3x)
= (10y) x (2y) + (10y) x (3x) + (2z) x (2y) + (2z) x (3x)
= 20y2+30yx+4zy+6zx
8
Find the product
(4y-x) ( 6x-y )

= 24yx-4y2-6x2+1xy
Solution
= (4y-x) x (6x-y)
= (4y) x (6x) - (4y) x (y) - (x) x (6x) - (x) x (y)
= 24yx-4y2-6x2+1xy
9
Find the product
(9a+b) ( 6a-6b )

= 54a2-48ab-6b2
Solution
= (9a+b) x (6a-6b)
= (9a) x (6a) - (9a) x (6b) + (b) x (6a) - (b) x (6b)
= 54a2-54ab+6ba-6b2
= 54a2-48ab-6b2
10
Find the product
(2x-2y) ( 5x-3y )

= 10x2-16xy-6y2
Solution
= (2x-2y) x (5x-3y)
= (2x) x (5x) - (2x) x (3y) - (2y) x (5x) - (2y) x (3y)
= 10x2-6xy-10yx+6y2
= 10x2-16xy-6y2
11
Find the product
(2x+3y) ( 5y-2z )

= 10xy-4xz+15y2-6yz
Solution
= (2x+3y) x (5y-2z)
= (2x) x (5y) - (2x) x (2z) + (3y) x (5y) - (3y) x (2z)
= 10xy-4xz+15y2-6yz
12
Find the product
(12y+4z) ( 2y+3z )

= 24y2+44yz+12z2
Solution
= (12y+4z) x (2y+3z)
= (12y) x (2y) + (12y) x (3z) + (4z) x (2y) + (4z) x (3z)
= 24y2+36yz+8zy+12z2
= 24y2+44yz+12z2
13
Find the product
(2x+4y) ( 9y-2z )

= 18xy-4xz+36y2-8yz
Solution
= (2x+4y) x (9y-2z)
= (2x) x (9y) - (2x) x (2z) + (4y) x (9y) - (4y) x (2z)
= 18xy-4xz+36y2-8yz
14
Find the product
(9a+2b) ( 6a+6b )

= 54a2+66ab+12b2
Solution
= (9a+2b) x (6a+6b)
= (9a) x (6a) + (9a) x (6b) + (2b) x (6a) + (2b) x (6b)
= 54a2+54ab+12ba+12b2
= 54a2+66ab+12b2
15
Find the product
(3a+4b) ( 2a+4b )

= 6a2+20ab+16b2
Solution
= (3a+4b) x (2a+4b)
= (3a) x (2a) + (3a) x (4b) + (4b) x (2a) + (4b) x (4b)
= 6a2+12ab+8ba+16b2
= 6a2+20ab+16b2
16
Find the product
(3x+3y) ( 4x+5y )

= 12x2+27xy+15y2
Solution
= (3x+3y) x (4x+5y)
= (3x) x (4x) + (3x) x (5y) + (3y) x (4x) + (3y) x (5y)
= 12x2+15xy+12yx+15y2
= 12x2+27xy+15y2
17
Find the product
(3x+5y) ( x-y )

= 3x2+2xy-5y2
Solution
= (3x+5y) x (x-y)
= (3x) x (x) - (3x) x (y) + (5y) x (x) - (5y) x (y)
= 3x2-3xy+5yx-5y2
= 3x2+2xy-5y2
18
Find the product
(x-4y) ( 2x+3y )

= 2x2-5xy-12y2
Solution
= (x-4y) x (2x+3y)
= (x) x (2x) + (x) x (3y) - (4y) x (2x) - (4y) x (3y)
= 2x2+3xy-8yx-12y2
= 2x2-5xy-12y2
19
Find the product
(7x-y) ( 9x-2y )

= 63x2-23xy-2y2
Solution
= (7x-y) x (9x-2y)
= (7x) x (9x) - (7x) x (2y) - (y) x (9x) - (y) x (2y)
= 63x2-14xy-9yx+2y2
= 63x2-23xy-2y2
20
Find the product
(15m-3n) ( 14m-16n )

= 210m2-282mn-48n2
Solution
= (15m-3n) x (14m-16n)
= (15m) x (14m) - (15m) x (16n) - (3n) x (14m) - (3n) x (16n)
= 210m2-240mn-42nm+48n2
= 210m2-282mn-48n2

## Worksheet: Multiplying Binomial by Binomial

Multiplying binomial by binomial worksheet is the largest collection of practice problems and solved exercises which can be served as homework, classwork or assignment problems for the students to learn, practice, assess, iterate and master the skills of how to solve such algebra problems in basic mathematics.

Online Test
00:00
Start my Challenge
Find the product (9n+8s) (8n+4s)
Find the product (5b+5c) (5b+6c)
Find the product (5a+7b) (a+8b)
Find the product (5q+7r) (7q+6r)
Find the product (4p+10q) (p+8q)
Find the product (10a-c) (9a+c)
Find the product (6b-9c) (9b-5c)
Find the product (3x-4y) (x-8y)
Find the product (6m+s) (5m-s)
Find the product (10x-z) (7x+z)

## Online Test: Multiplying Binomial by Binomial

This online test to find the multiplying binomial by binomial is a formative assessment which can be used as homework, classwork or assignment problems to assess and improve the learner's math skills on algebra.